The Comparison Word Wall and Crossword Puzzle in Improving Students’ Vocabulary - Marni, Marni; Suryadi, Suryadi; Ediwarman, Ediwarman (Journal Of Teaching And Learning In Elementary Education, 2024)
This article shows the results of research that tries to compare the word wall and crossword puzzle in improving students' vocabulary at Mangkunegara Elementary School for the 2023/2024 academic year, located in Mangkunegara Village, Bojonegara District, Serang Regency, Banten. For the purpose of this topic, 24 students were selected as samples, while the population of this study was 140 students. The research method used was quasi-experimental with a posttest-only control group design. Based on the results of average calculations, standard deviation tests, normality tests, homogeneity tests, and t-tests to examine the data, The findings show that using Word Wall has a significant positive influence on increasing students' vocabulary in terms of Word Wall media (x ̅ = 41.66, s = 18.38) had a greater influence than the group that used Crossword Puzzle (x ̅ = 41.66, s = 14.82). In short, word walls are an effective way to teach students vocabulary mastery. The implication of carrying out this research is to provide treatment in the form of a list of words on a word wall to class V students at SDN Mangkunegara. This teaching strategy can help students improve vocabulary mastery.